2020
DOI: 10.5018/economics-ejournal.ja.2020-23
|View full text |Cite
|
Sign up to set email alerts
|

Offshoring, job satisfaction and job insecurity

Abstract: This paper investigates the effects of offshoring on individual job satisfaction and perceived risk of job loss. The authors merge microdata from the German Socio-economic Panel dataset (SOEP) with indicators of insertion in global value chains at the industry level for the period 2000-2013. They test two hypotheses. First, the authors investigate whether workers in industries with higher offshoring intensity report lower job satisfaction and/or are more prone to be unsecure at their jobs. Second, they test wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Heidarian et al (2015) found female employees had little opportunity to participate in goal setting and decision making. On the other hand, Budría & Baleix (2020); Azad et al, (2011); and Ali and Akhter (2009) found that there is no significant difference between male and female employees' job satisfaction.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Heidarian et al (2015) found female employees had little opportunity to participate in goal setting and decision making. On the other hand, Budría & Baleix (2020); Azad et al, (2011); and Ali and Akhter (2009) found that there is no significant difference between male and female employees' job satisfaction.…”
Section: Discussionmentioning
confidence: 96%
“…When workers are free to decide how to develop and organize their work, they often feel more satisfied and committed to their job (Islam, 2016). High employee satisfaction will strengthen and support the workforce, make employees more creative and innovative and produce superior performance and productivity in optimal time, diminish absenteeism and turnover intention, reduce accident, stress, and work performance as a whole improves (Budría & Baleix, 2020;Asadullah et al, 2019;Rahman, 2020), thus it increases productivity and profits (Farrell and Stamm, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…In his research on employees who work in offshore areas, it is found that working in offshore areas gives employees lower job satisfaction compared to workers that work in the office. The intensity of work in the offshore area negatively impacts job satisfaction among workers (Budría & Baleix, 2020). Within their research on 120 self-financing university professors, there are positive relationships between the ethical climate of certain workplaces and job satisfaction (Kamalaselvi & Mahalakshmi, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Intense production for GVCs has raised new concerns about working conditions and the protection of workers' rights (Delautre et al 2021). Yet GVC-focused research has rarely dealt with such aspects of work as health and occupational safety, job satisfaction or job security (Budría and Milgram Baleix 2020;Geishecker 2012). Even if the social consequences of GVCs are analysed, they are mainly quantified in terms of their impact on wages or risk of job displacement (Baumgarten et al 2013;Ebenstein et al 2014;Geishecker et al 2010;Wolszczak-Derlacz 2019, 2020;Shen and Silva 2018;Hummels et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, Lloyd and James (2008) report the positive impact of GVCs on the health and safety of workers employed in the UK food processing industry. Budría and Milgram Baleix (2020) investigate the effects of production fragmentation on individual job satisfaction and perceived risk of job loss among German workers, finding that offshoring is negatively associated with job satisfaction.…”
mentioning
confidence: 99%